(untitled) (Research, Society and Development, 2022)
Objective: To verify the main factors related to vaccine adherence and hesitation in adults from the general population. Methodology: This is an integrative literature review carried out in October 2021 in the Medical Literature Analysis and Retrievel System Online (MEDLINE) databases via the National Library of Medicine National Institutes of Health (PubMed), Scopus, Latino- American and Caribbean in Health Sciences (LILACS) and Web of Science. The guiding question of the research was: “What are the factors related to adherence and vaccine hesitation in adults in the general population?”. Results: 30 scientific articles were eligible for review, and were grouped into three subgroups according to the factors related to adherence and hesitation addressed in the article: Trust/knowledge in relation to vaccines and/or health system (14 articles, 45.2%); Socioeconomic factors (10 articles, 32.2%); and Other factors (07 articles, 22.6%). Conclusion: The data obtained can contribute to the development of public health education strategies in order to increase adherence to individual immunization, favoring collective protection.